Mirror image analysis of websites of universities for academic innovation-comparison among south east and south asian top-100s - Barman, Arup (Journal of Management and Science, 2013)
Educational institutions of developing country are in the reverie for cyber world through the launch of website to connect and reconnect to the info-academic world. Educational institutions with tradition posting institutional information on a web never place themselves in the global picture. To place as a top ranked institution in global institutional web map demand visibility, richness of contents, and faculty strength which are known as knowledge enablers.When an institution thinks about innovation of knowledge and display contents of universities then must have to think critically in terms of innovation of these knowledge enablers. South Asian including Indian academic institutions are emphasizing on integration to the cyber world with a dream to become player in the emerging knowledge hub. To become a knowledge hub Indian Institution must have to develop its website for greater visibility. Side by side, researchers and intellectuals must realize the significance of launching the institutional websites for integration of administration, knowledge repositories and class rooms.This study examines and compares the state of South Asian Top-100, South East Asian Top-100. In examining the ranks of 100 Asian Universities Webo-metrics data compared the level of concordance (ranking agreements) and mirror images. The concordances and mirrors images revealed the direction of relationship of variables of knowledge enablers and finally attempts to identify the cues for innovation with the help of web site to launch the websites by South Asian Institutions